Pembuatan Media Pembelajaran Fisika Berbasis Augmented Reality Menggunakan Vuporia - Demmy Dharma Bhakti; Yopi Nugraha; Purnomo Sidiq (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2020)
Teachers are required to improve their abilities in the field of technology by utilizing ICT to communicate and develop themselves. Teaching materials in the form of innovative learning media utilizing information technology in accordance with the development needs of students is one of the things that can be used by teachers in answering the mandate of the Law on Teachers and Lecturers. Augmented Reality is one of the results of current developments in information technology which is seen as helping in the learning process of some learning materials, especially abstract concepts. This community service activity (PkM) aims to improve teacher professional competence through augmented reality based teaching materials development training using the Vuporia application, which in practice uses the lecture method, discussion method, and group design methods. This PkM activity is targeted for 20 participants with consideration of current conditions that are being hit by the Covid 19 pandemic, and is adjusted to comply with the Covid 19 health protocol. The participants who attended were 11 participants who were physics teachers who were members of the SMK physics MGMP. Garut Regency. The PkM activity has succeeded in opening new insights for physics teachers who are training participants in delivering material in class, and have been able to make physics learning media based on Augmented reality using Vuporia